2017
DOI: 10.1111/1365-2656.12665
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of coinfection: trematodes alter disease outcomes associated with virus infection

Abstract: Coinfections are increasingly recognized as important drivers of disease dynamics. Consequently, greater emphasis has been placed on integrating principles from community ecology with disease ecology to understand within-host interactions among parasites. Using larval amphibians and two amphibian parasites (ranaviruses and the trematode Echinoparyphium sp.), we examined the influence of coinfection on disease outcomes. Our first objective was to examine how priority effects (the timing and sequence of parasite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 49 publications
4
68
0
Order By: Relevance
“…Previous studies have reported a similar correlation between viral load and mortality (Wuerthner et al., 2017). Our results suggest that regardless of population, wood frogs experience mortality when log viral loads passed a threshold of approximately 5 viral copies/ng of DNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported a similar correlation between viral load and mortality (Wuerthner et al., 2017). Our results suggest that regardless of population, wood frogs experience mortality when log viral loads passed a threshold of approximately 5 viral copies/ng of DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that regardless of population, wood frogs experience mortality when log viral loads passed a threshold of approximately 5 viral copies/ng of DNA. A similar threshold was detected when log viral loads approached 4.5 viral copies/ng of DNA in gray tree frogs ( Hyla versicolor ; Wuerthner et al., 2017). Identifying a threshold value can potentially allow researchers to make predictions about the likelihood or timing of a ranavirus die‐off in natural populations.…”
Section: Discussionmentioning
confidence: 99%
“…For each individual, we pooled the liver and kidney tissues and extracted DNA using DNeasy Blood and Tissue Kits (Qiagen). To quantify infection status for each individual, we used quantitative polymerase chain reaction (Wuerthner, Hua, & Hoverman, ). Our qPCR mixture included a 1.0 μl mixture of each primer at 10 pmol/μl (rtMCP‐F [5′‐ACA CCA CCG CCC AAA AGT AC‐3′] and rtMCP‐R [5′‐CCG TTC ATG ATG CGG ATA ATG‐3′]), and a fluorescent probe (rtMCP‐probe [5′‐CCT CAT CGT TCT GGC CAT CAA CCA‐3′]), and 6.25 μl of TaqMan ® Universal PCR Master Mix (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…For each individual, we pooled the liver and kidney tissues and extracted DNA using DNeasy Blood and Tissue Kits (Qiagen). To quantify infection status for each individual, we used quantitative polymerase chain reaction (Wuerthner, Hua, & Hoverman, 2017). | 641 fluorescent probe (rtMCP-probe [5 0 -CCT CAT CGT TCT GGC CAT CAA CCA-3 0 ]), and 6.25 ll of TaqMan â Universal PCR Master Mix (Applied Biosystems).…”
Section: Field Sampling and Measurements During Site Visitsmentioning
confidence: 99%
“…Interactions between parasite occurrence, habitat degradation, and chemical exposure introduce further complications in assessment of vulnerability (Koprivinkar and Redfern 2012;Stutz et al 2017) with the potential for agrochemicals to reduce immunity to parasite infection (Kiesecker 2002;Rohr et al 2008) and decrease parasite survival (Hua et al 2016). Multiple parasites do not always produce synergistic effects; compensatory effects of coinfection are also possible (Wuerthner et al 2017). Positive identification of B. dendrobatidis in national field samples has been associated with dissolved organic content, total N, and P as well as cooler water temperatures (Battaglin et al 2016).…”
Section: Discussionmentioning
confidence: 99%